Determining the time points for the development of early and advanced stages of diabetic cardiomyopathy in streptozotocin-induced type 1 diabetes mellitus rat model - Fatin Farhana Jubaidi; Nur Liyana Mohammed Yusof; Satirah Zainalabidin; Izatus Shima Taib; Zariyantey Abd Hamid; Siti Balkis Budin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The characteristics of early and advanced stages of diabetic cardiomyopathy (DCM) are well-understood; however, the time points by which these stages are developed in animal models vary and depend on the hyperglycaemic status and duration of diabetes. This study was aimed to determine the time points for the development of early and advanced stages of DCM from the induction of type 1 diabetes mellitus by identifying the functional and histological changes that occurred. Type 1 diabetes was induced via streptozotocin injection, and rats were divided into 4-week and 8-week diabetic groups. A group of non-diabetic rats served as the normal control. Cardiac functions and structural changes were analysed. Results showed that after four weeks, all diabetic rats displayed early DCM characteristics, including pronounced left ventricular diastolic dysfunction and cardiomyocyte hypertrophy (P < 0.05) compared to the normal control. After eight weeks, there was a significant deterioration in both left ventricular systolic and diastolic function compared to the normal control, along with marked cardiomyocyte hypertrophy and myocardial fibrosis (P < 0.05), signifying the development of advanced DCM. In summary, this findings revealed the development of early and advanced stages of DCM at four weeks and eight weeks of diabetes respectively in diabetes melitus type 1 rat model.